Endline Study Report and Policy Study for the ConVERGE Project - Roehlano M. Briones; Ivory Myka R. Galang; Isabel B. Espineli; Aniceto C. Orbeta; Marife Magno-Ballesteros (Philippine Institute for Development Studies (PIDS), 2023)
The Department of Agrarian Reform (DAR), in partnership with the International Fund for Agricultural Development (IFAD), implemented the project "Convergence on Value Chain Enhancement for Rural Growth and Empowerment" or Project ConVERGE with the goal of empowering Agrarian Reform Beneficiaries (ARBs) to drive rural economic growth across 10 provinces spanning three regions. DAR engaged the Philippine Institute for Development Studies (PIDS) to undertake baseline and endline studies, serving as a crucial assessment tool for the project's performance and providing insights to inform the comprehensive ARC Cluster Development (ARCCD) Strategy aimed at advancing smallholder agriculture in the Philippines. This Endline Report provides the analysis of the baseline and endline datasets. It discusses the following key points: i) results of the impact evaluation study; ii) result of final process evaluation; and iii) recommendations for the Agrarian Reform Communities Cluster Development (ARCCD) Strategy. The quantitative analysis part of the study indicates a significant 41% average treatment effect from the Project, validating its Theory of Change in boosting income for ARC cluster households through value chain interventions. The process evaluation generally confirms the assumptions and impact pathways, with some deviations and shortfalls. Beneficiaries express satisfaction with the Project but have limited understanding of its rationale. The clustering method, which links small farmers to value chains by forming agrarian reform beneficiaries (ARBs) into lead and participating ARB organizations (ARBOs), appears to enhance government support efficiency for organized groups. The paper underscores the importance of additional capacity building for both LARBOs and PARBOs, and it recommends a more active engagement of other government agencies to address value-adding technologies, food processing standards, credit accessibility, and market facilitation.
Keywords: 330; agrarian reform beneficiary organizations; ARBOs; ARBs; DAR; IFAD; ConVERGE; value chains; treament effects; endline; baseline; Agrarian Reform Communities Cluster Development; ARC; ARCCD; Mindanao; clustering; cluster; impact evaluation; difference-in-difference; regression; process evaluation